Accounting Theory Structure as A Basis for Developing a Financial Reporting Framework - Yuyun Lestari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
Accounting theory plays a fundamental role in establishing systematic and consistent accounting and financial reporting practices. This study aims to examine the definition, scope, and structure of accounting theory and its relationship to the conceptual framework for financial reporting developed by the International Accounting Standards Board (IASB). This study focuses on the role of accounting theory as a philosophical and conceptual foundation for establishing financial reporting standards, as well as the function of the conceptual framework as a translator of theory into accounting practice. The approach used is a conceptual study by analyzing academic literature, scientific journals, and relevant official documents. The results of the study indicate that the structure of accounting theory, which includes reporting objectives, basic assumptions, concepts, and accounting principles, plays a crucial role in building a coherent conceptual framework, reducing uncertainty in accounting practices, and supporting the development and evaluation of financial reporting standards. The integration of accounting theory and the conceptual framework has been shown to improve the quality, consistency, and usefulness of financial information for stakeholders in facing the dynamics of the modern business environment.